Increasing Rates of Invasive Group A Streptococcal Disease in Alberta, Canada; 2003–2017. (20th July 2018) - Tyrrell, Gregory J; Fathima, Sumana; Kakulphimp, Jocelyne; Bell, Christopher
Abstract: Background: We present an analysis of increasing rates of invasive group A streptococci (iGAS) over a 15-year period in Alberta, Canada. Methods: From 2003 to 2017, the emm type of iGAS isolates was identified from patients with iGAS disease in Alberta. Demographic, clinical, and risk factor data were collected. Results: A total of 3551 cases of iGAS were identified in Alberta by isolation of a GAS isolate from a sterile site. The age-standardized incidence rates of iGAS increased from 4.24/100 000 in 2003 to 10.24 in 2017. Rates (SD) were highest in those age <1 (9.69) years and 60+ (11.15) years; 57.79% of the cases were male. Commonly identified risk factors included diabetes, hepatitis C, nonsurgical wounds, addiction, alcohol abuse, drug use, and homelessness. The overall age-standardized case fatality rate was 5.11%. The most common clinical presentation was septicemia/bacteremia (41.84%), followed by cellulitis (17.25%). The top 4 emm types from 2003–2017 were emm 1, 28, 59, and 12. In 2017, the top 4 emm types ( emm 1, 74, 101, and 59) accounted for 46.60% of cases. Conclusions: The incidence of iGAS disease in Alberta, Canada, has increased from 2003 to 2017. This increase has been driven not by a single emm type, but rather what has been observed is a collection of common and emerging emm types associated with disease. In addition, it is also likely that societal factors are playing important roles in this increase as risk factors associated with marginalized populations (addiction, alcohol abuse, and drug use) were found to have increased during the survey period.